Discovery and structure–activity relationships of a novel isothiazolone class of bacterial type II topoisomerase inhibitors. Issue 17 (1st September 2016) - Cooper, Ian R.; McCarroll, Andrew J.; McGarry, David; Kirkham, James; Pichowicz, Mark; Walker, Rolf; Warrilow, Catherine; Salisbury, Anne-Marie; Savage, Victoria J.; Moyo, Emmanuel; Forward, Henry; Cheung, Jonathan; et al.
Graphical abstract: Abstract: There is an urgent and unmet medical need for new antibacterial drugs that tackle infections caused by multidrug-resistant (MDR) pathogens. During the course of our wider efforts to discover and exploit novel mechanism of action antibacterials, we have identified a novel series of isothiazolone based inhibitors of bacterial type II topoisomerase. Compounds from the class displayed excellent activity against both Gram-positive and Gram-negative bacteria with encouraging activity against a panel of MDR clinical Escherichia coli isolates when compared to ciprofloxacin. Representative compounds also displayed a promising in vitro safety profile.